Trends and issues in science education in the new millennium: A bibliometric analysis of the JRST - DOĞAN, ÖZGÜR KIVILCAN (My University, 2023)
As a real time socio-scientific issue, the COVID-19 pandemic has clearly shown us the need for the public to understand science. As experts have repeatedly stressed in recent years, science education plays an important role in developing scientifically literate societies. In this context, it is critical to consider which subjects science educators frequently concentrate on and the messages they give to researchers, policymakers, and other stakeholders. Therefore, the purpose of this study was to use bibliometric data to understand the topics that the articles in the Journal of Research in Science Teaching (JRST), one of the flagship journals about science education and teaching, focused on over the last 20 years. This study employed both descriptive and bibliometric analysis. Based on data from the Web of Science (WoS), descriptive analyses are presented as frequencies and percentages and we used VOSviewer software for bibliometric analysis. Findings showed that more than 80% of the authors of the JRST are from the United States, Australia, Canada, and the United Kingdom. Moreover, results of these analyses demonstrate that the researchers publishing in the JRST focused on two main ideas over the past 20 years: “Which science teaching methods and strategies are most effective?” and “What can be done to make science teaching more inclusive?” As a result, it can be clearly seen that JRST has special attention on inclusive approach in science education which should be designed to include traditionally underrepresented groups.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Fen Bilimleri Eğitimi; Social Sciences and Humanities; Education; Education in Natural Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Bibliometric Analysis; JRST; Inclusive Education; Science Education